Loop-mediated isothermal amplification (LAMP) assays for the species-specific detection of Eimeria that infect chickens - Barkway, Christopher P (BioMed Central, 2011)
BACKGROUND: Eimeria parasites can cause the disease coccidiosis in poultry and even subclinical infection can incur economic loss. Diagnosis of infection predominantly relies on traditional techniques including lesion scoring and faecal microscopy despite the availability of sensitive molecular assays, largely due to cost and the requirement for specialist equipment. Despite longstanding proven efficacy these traditional techniques demand time and expertise, can be highly subjective and may under-diagnose subclinical disease. Recognition of the tight economic margins prevailing in modern poultry production and the impact of avian coccidiosis on poverty in many parts of the world has highlighted a requirement for a panel of straightforward and sensitive, but cost-effective, Eimeria species-specific diagnostic assays. RESULTS: Loop-mediated isothermal amplification (LAMP) is an uncomplicated, quick and relatively inexpensive diagnostic tool. In this study we have developed a panel of species-specific LAMP assays targeting the seven Eimeria species that infect the chicken. Each assay has been shown to be genuinely species-specific with the capacity to detect between one and ten eimerian genomes, equivalent to less than a single mature schizont. Development of a simple protocol for template DNA preparation from tissue collected post mortem with no requirement for specialist laboratory equipment supports the use of these assays in routine diagnosis of eimerian infection. Preliminary field testing supports this hypothesis. CONCLUSIONS: Development of a panel of sensitive species-specific LAMP assays introduces a valuable new cost-effective tool for use in poultry husbandry.